Faktor-Faktor yang Mempengaruhi Kinerja Usaha Mikro di Kota Palembang - mardalena mardalena; Eriyanto Eriyanto (Universitas Bengkulu, 2021)
This study aims to determine the effect of productive zakat, age, education, length of business and business location on the performance of micro-enterprises in Palembang City. The data used in this study are primary data with a sample of 30 micro enterprises. Determination of the sample in this study using the random sampling method. The analytical method used is descriptive analysis and multiple linear analysis or Ordinary Least Square (OLS). The results of the analysis show that the productive zakat, age, education, length of business and business location variables simultaneously affect the performance of micro-businesses in Palembang City. The productive zakat variable has a positive and significant effect, the age and education variable has a negative and insignificant effect, the length of business variable has a positive but insignificant effect, and the business location variable has a negative and significant effect on the performance of micro-businesses in Palembang City.